SURVEY KONDISI ATLET FISIK PENCAK SILAT PADA UKM PENCAK SILAT STKIP ROSALIA LAMPUNG - Luh Eka Laba; Rudy Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the level of physical condition of pencak silat athletes at UKM Pencak Silat STKIP Rosalia Lampung. This study uses a quantitative approach. This type of research is a survey. The population is 18 athletes and the sample of this study is 18 athletes taken using the total sampling technique. Data collection techniques are carried out by testing strength, speed, flexibility, agility, explosive power and balance tests. Data analysis uses the average formula and frequency distribution. Based on the results of data processing, it is known that the level of physical condition of pencak silat athletes at UKM STKIP Rosalia Lampung in terms of physical strength is classified as moderate, physical speed is in the moderate category, physical flexibility is in the good category, physical agility is in the above average category, physical explosive power is in the good category and physical balance is in the average category.